2015
DOI: 10.1007/s10006-015-0490-9
|View full text |Cite
|
Sign up to set email alerts
|

Severe maxillofacial renal osteodystrophy in two patients with chronic kidney disease

Abstract: Renal osteodystrophy (ROD) is the bone pathology that occurs as an uncommon complication related to the several alterations in mineral metabolism present in patients with chronic kidney disease (CKD). This paper describes two cases of severe ROD affecting the maxilla and mandible and causing facial disfigurement of a young and a middle-aged female patient with CKD. Both patients had a history of secondary hyperparathyroidism, previously treated by surgery. The pathogenesis of the disease, as well as its clinic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 22 publications
(47 reference statements)
1
4
0
Order By: Relevance
“…Radiographic changes in RO are similar to the changes observed in fibrous dysplasia or Paget's disease. This pathophysiology is consistent with ground-glass bone appearance, hypercementosis and bone resorption with loss of the lamina dura [25]. The latter is a common dental radiographic feature for all high-turnover metabolic bone diseases.…”
Section: Dental Manifestationssupporting
confidence: 75%
“…Radiographic changes in RO are similar to the changes observed in fibrous dysplasia or Paget's disease. This pathophysiology is consistent with ground-glass bone appearance, hypercementosis and bone resorption with loss of the lamina dura [25]. The latter is a common dental radiographic feature for all high-turnover metabolic bone diseases.…”
Section: Dental Manifestationssupporting
confidence: 75%
“…Bakathir et al [15] described the progressive enlargement of facial bones of a 21-year-old female uremic patient whose facial enlargement involved the maxilla and caused facial and dental deformities. Lopes et al [16] presented two female uremic patients with facial disfigurement affecting the maxilla and the mandible. Raubenheimer et al [17] also reported two female uremic cases with extensive jaw lesions due to secondary hyperparathyroidism.…”
Section: Discussionmentioning
confidence: 99%
“…Renal bone disease causes cranial and maxillofacial appearance changes due to maxillary fibrosis deformity. Lopes et al 29 reported two cases of severe renal osteodystrophy affecting the maxilla and mandible, ultimately causing facial disfigurement in a young female patient with CKD and a middle-aged female patient with CKD. Severe bone changes in the skull and maxillofacial face are accompanied by abnormal bone metabolism in other sites, which are characterized as Sagliker syndrome 4 .…”
Section: Discussionmentioning
confidence: 99%